Viewing television in media convergence era Rites change and practices transformation - labane, aziz (ALBAHITH ALALAMI, 2019)
The present article concerns one of the objects of media sociology under construction. The transformation of the rites in the use of the television contents in the era of digital technologies and media convergence. By an analytic contextual approach, based on the study of the uses, we formulate the following hypothesis: so many changes in the rites of uses are real, in particular at the young people, so, many pieces integer of the everyday life remain impervious to these changes, and it is true under the influence of a slowness of the social and cultural orders, rooted for a long time in the traditional social fabric. We shall then try to bring a sociological look to this societal, cultural, and communicational object that is the passage of the reception television contents in the various digital platforms. This passage stands out nevertheless, a transformation in the media: the passage from the collective viewing in family to the personalized individual viewing. Sociological dimension which underlies this transformation has for consequence the dismantling of the temporal structure of the consumption, by giving the possibility to the users to reorganize the television appointment, and to release them at the same time from the domestic space, the place where the practices are applies the social control by means of the interactions public television. « Old media are not beingdisplaced .Rather, their functions and statuses are shifted by the introduction of new technology.”(Jenkins, 2006)